Análise do desgaste superficial e efeito do polimento no esmalte dental microabrasionado - Pedro, Maíra Fernanda Bardi [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
This treatment leads to wear away of the enamel. Therefore, it is very important to understand several microabrasion treatment options current available. In this context, the aim of the present study is to comparatively evaluate the detritions caused by different microabrasive agents and polishing effect. In attempt, 40 enamel bovine fragments were divided in four randomized groups (n=10) depending on the used microabrasive agent: GI- phosphoric acid (37%) plus pumice; GII- chloride acid (12%) plus pumice; GIII- Microabrasive Whiteness RM (FGM) and GIV- Opalustre (Ultradent). Following, the samples were submitted to 8 applications with the different microabrasive agents for 15 seconds using a rubber cup coupled to contra-angle. The specimens were washed in running water between applications. After microabrasion and final polishing, enamel teeth superficies were analyzed, allowing the determination of the erosion. Obtained data were submitted to ANOVA followed by Fisher post-test with P<0.05. The results showed that groups GI and GIV preset higher erosion in the superficie and GII presents lesser erosion. The Polishing produced to wear do not interfere in outcome. In conclusion, the acid phosphoric plus pumice and Opalustre lead to higher erosion in teeth enamel

Este trabalho tem como objetivo avaliar comparativamente o desgaste superficial provido por diferentes agentes microabrasivos e o efeito do polimento. Para tanto, 40 fragmentos de esmalte bovino foram divididos aleatoriamente em quatro grupos (n=10), conforme o microabrasivo empregado: GI- Ácido fosfórico a 37% + pedra pomes; GII- Ácido clorídrico a 12% + pedra pomes; GIII- Microabrasivo Whiteness RM (FGM); GIV- Opalustre (Ultradent). Os corpos de prova foram submetidos a 08 aplicações de 15 segundos dos agentes microabrasivos em estudo, com auxílio de uma taça de borracha acoplada ao contra-ângulo. Entre as aplicações, os espécimes foram lavados em água corrente. Após a microabrasão, bem como após o polimento final dos dentes foram realizadas leituras da superfície do esmalte, possibilitando avaliar o desgaste ocorrido. Os dados obtidos foram submetidos aos testes de ANOVA e de Fisher com significância de 5%. Os resultados mostraram que os grupos GI e GIV apresentaram maior desgaste superficial, enquanto grupo GII apresentou os menores valores. O polimento não interferiu nos resultados. Concluiu-se que os produtos ácido fosfórico com pedra pomes e o Opalustre proporcionaram maior desgaste do esmalte dental
Keywords: Microabrasão do esmalte; Desgaste dos dentes; Polimento dentário; Enamel Microabrasion